Determinants of Dividend Policy in Nigerian Banks - Ndukwe O. Dibia (Archives of Current Research International, 2018)
The focus of this study was to provide research-based- evidence on the influence of certain variables on dividend policy using Nigerian banks. Specifically, the study examines the effects of profitability, firm size, leverage and previous levels of dividend payout on dividend policy. Using fifteen banks with data period spanning 2006-2013 and employing the fixed effects regression estimates, our results show the effect of profitability on dividend policy, we found that ROA is positive and significant at 5%. The positive sign as expected suggests that profitable firms will pay dividends. However, the possibility of an inverse relationship as observed for ROE is also likely in two scenarios; (i) In situations where less cash flow is expected in the future a firm pays less and (ii) where the firm has investment opportunities. Firm size (FSIZE) is positive and significant at 5%. Leverage (LEV) appeared negative and also significant in line with aprori expectation. Previous period dividend DIV (-1) is positive though not significant at 5%. The study recommends that no doubt companies have corporate incentives to engage in dividend announcements and since the market value responds favourably. However, the study recommends further especially for the benefits of potential investors that given the widespread abuse of Dividends amongst companies it is increasingly becoming difficult to distinguish between "good" and "bad" companies solely by depending on which is paying dividends and hence investors should also border to investigate the company’s fundamentals.